Leadership in English language teaching and learning - Coombe, Christine A. (Christine Anne), 1962-; McCloskey, Mary Lou; Stephenson, Lauren; Anderson Neil J. (Ann Arbor : University of Michigan Press, 2011)
Leadership skills are indispensable in language teaching and learning. This title provides theoretical underpinnings of leadership development; the leadership skills and strategies on the topics of interpersonal communication, personal organization skills, and program organization skills; and issues relevant to ELT leadership in US public schools.
Includes bibliographical references and indexes.
BIL
Pay the bill to Lady Syeda Sarwat Abed, Director, BIL, BRAC University
Keywords: English language -- Study and teaching -- Foreign speakers; Educational leadership; English teachers -- Training of